PEMBERDAYAAN MASYARAKAT MELALUI PENYUSUNAN TARI BOTHOKLO SEBAGAI IKON DESA WISATA LEMBAH DUNGDE DESA MLILIR, KALURAHAN GENTUNGAN, KEC. MOJOGEDANG, KABUPATEN KARANGANYAR - Dwi Wahyudiarto; Anggono Kusumo Wibowo; Dwi Rahmani (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2022)
Abstract Community Empowerment through the Bothoklo Dance as an Icon of the Dungde Valley Tourism Village, Mlilir Village, Gentungan Village, Mojogedang District, Karanganyar Regency, is an accompaniment program to the community as a tangible manifestation of the implementation of the Vision of the Indonesian Institute of the Arts Surakarta. The preparation of Bothoklo Dance as an icon of a tourist village, comes from the traditional culture of the Mlilir Village community. The preparation process is carried out with the community, this is a form of creative creative education so that the community awakens its creative spirit. The method used in the preparation of the Bothoklo dance is the three R method, namely Re-Visiting, Re-Questioning and Re-Interpreting. The results of the preparation of the Botoklo Dance are then trained to the community as a strengthening of tourist attraction. The training was carried out in the Dungde Valley Tourism Village, Mlilir Village, Gentungan Village. This is intended to be closer and introduce the Surakarta Indonesian Art Institute campus to the public. In addition, the form of training with the community can also be an attraction for the community / tourists who come to the Dungde Valley. The result of this community empowerment is the composition of the Bothoklo Dance with the theme of mythological animals in Mlilir Village, packaged in the form of group dance. The music used is a variety of ethnic groups in the Mlilir area, while the clothing uses the artistic rods of mendong with the current packaging. Bothoklo dance is taught to the Mlilir community to be developed as a tourist village icon.